Effect of Taping of Thoracic and Abdominal Muscles on Pelvic Alignment and Forward Reach Distance Among Stroke Subjects: A Randomized Controlled Trial. Issue 3 (July 2019) - Mehta, Megha; Joshua, Abraham M.; Karthikbabu, Suruliraj; Misri, Zulkifli; Unnikrishnan, Bhaskaran; Mithra, Prasanna; Nayak, Akshatha
Abstract: Introduction: The objective of this study was to find the immediate as well as short-term effect on pelvic alignment and forward arm reach distance in sitting among stroke patients following thoracic spine and abdominal muscles taping along with conventional therapy. Methods: Thirty subjects with stroke attending the physiotherapy programme at Department of Physiotherapy at a tertiary care hospital underwent this randomized controlled experimental study. Subjects in the experimental group received taping, along with conventional physiotherapy treatment, for restricting thoracic kyphosis and facilitating abdominal muscles. Subjects in the control group received only conventional physiotherapy treatment. To assess the change in pelvic alignment and forward arm reach distance while sitting, Palpation Meter TM (PALM TM ) and sit and reach test were used, respectively. Results: In the experimental group, pelvic obliquity was corrected (4.1 ± 0.94) and anterior pelvic tilt revealed improvement (4.9 ± 2.1, p value < 0.001). In the control group, no improvement in pelvic alignment was recorded. Improvement in forward arm reach distance was similar in both groups ( p value = 0.804). Conclusion: Taping as an adjunctive treatment method to physiotherapy can cause immediate as well as short-term improvement of pelvic alignment in sitting, following stroke. It also, immediately improves the sit and reach distance in the same population.